Alternative therapeutic approaches for combating multi-drug-resistant bacteria: Reverse vaccinology against Enterobacter cloacae - Gabriela Guerrera Soares; Marcelo Silva Folhas Damas; Pedro Mendes Laprega; Rebecca Elizabeth Shilling; Eduarda Oliva Ribeiro Rangel; Louise Teixeira Cerdeira; Murillo Rodrigo Petrucelli Homem; André Pitondo-Silva; Andrea Soares da Costa-Fuentes; Maria-Cristina da Silva Pranchevicius (Journal of Genetic Engineering and Biotechnology)
Enterobacter cloacae is a clinically significant opportunistic and multidrug-resistant bacterium that causes a range of hospital-acquired infections, particularly in intensive care units. However, studies on vaccine development have been limited, and no vaccine currently protects against E. cloacae. Here, we employed subtractive proteomics, reverse vaccinology, and immunoinformatic approaches to design a multi-epitope-based vaccine targeting E. cloacae. Analysis of 21 complete E. cloacae genomes associated with human infections revealed 1,352 proteins linked to essentiality, resistance, and/or virulence, 39 of which were non-human and non-gut homologs. From this refined selection, 9 were found to be antigenic, extracellular, or exported to the outer membrane and used to construct 4 multi-epitope vaccines (VEC1-4) containing antigenic (threshold of ≥0.5), non-allergenic, conserved, hydrophilic (GRAVY < 0), exposed, and non-toxic epitopes. They were all processed and presented through the MHC class pathway, while also showing high population coverage. VEC1 showed the most consistent performance, with the highest average binding affinity (−24.07 kcal/mol), docking score (−322.21), and the most favorable dissociation constant at 37 °C. VEC1 was shown to be conformationally stable, with a secondary structure predominantly made up of alpha-helices and coils. The in silico analysis suggested that VEC1 can be efficiently expressed in an E. coli system, and it is currently awaiting in vivo testing to confirm its precise efficacy, safety, and immunogenicity. These findings provide valuable insights for developing novel approaches to prevent and control the spread of multidrug-resistant bacteria.